Africa's Ogun : old world and new - Barnes, Sandra T. (African systems of thought., 1997)
The second edition of this landmark work is enhanced by new chapters on Ogun worship in the New World. From reviews of the first edition: ... an ethnographically rich contribution to the historical understanding of West African culture, as well as an exploration of the continued vitality of that culture in the changing environments of the Americas."--African Studies Review ... leav[es] the reader with a sense of the vitality, dynamism, and complexity of Ogun and the cultural contexts in which he thrives ... magnificent contribution to the literature on Ogun, Yoruba culture, African religions, and the African diaspora." -- International Journal of Historical Studies